2004
DOI: 10.1080/03014460412331281719
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal timing and educational careers: a longitudinal study

Abstract: Early or average onset of puberty plays a role in dividing boys into educational tracks after compulsory schooling. Support should be given to boys, whose delayed pubertal development makes them immature to making appropriate educational decisions and to boys who may have experienced early puberty but fail to exploit educational opportunities available for them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 38 publications
1
18
1
2
Order By: Relevance
“…Whether this factor is relevant for the study presented herein is only speculative and needs to be investigated in more detail in future studies. It has been reported that delayed pubertal development in boys is associated with reduced ability to make appropriate educational decisions [24] which would, however, not explain our findings. The re-analysis of BMI, skinfold thickness and body fat adjusting for testicular volume and breast size was important because it demonstrated that increased body fat mass is associated with the level of education independently of pubertal stage.…”
Section: Discussioncontrasting
confidence: 56%
“…Whether this factor is relevant for the study presented herein is only speculative and needs to be investigated in more detail in future studies. It has been reported that delayed pubertal development in boys is associated with reduced ability to make appropriate educational decisions [24] which would, however, not explain our findings. The re-analysis of BMI, skinfold thickness and body fat adjusting for testicular volume and breast size was important because it demonstrated that increased body fat mass is associated with the level of education independently of pubertal stage.…”
Section: Discussioncontrasting
confidence: 56%
“…Girls who experience early maturation are more likely to obtain lower SES employment and transmit earlier ages of development to their daughters. Although research in this area is sparse, the inclusion of socioeconomic demographics into analyses seems to eliminate associations between early menarche and educational attainment (Koivusilta & Rimpela, 2004).…”
Section: Academic Achievementmentioning
confidence: 99%
“…To obtain an indicator of pubertal timing (biological pathway), boys were asked about their age at first ejaculation, while girls were asked about their age at menarche. Classification of pubertal timing as early, average and late followed the groupings used by Koivusilta and Rimpel€ a (2004). In boys, the categories were chosen to be at age 12 or earlier (early), at 13 or 14 (average), and at 15 or later or if not occurred by the time of enquiry (late).…”
Section: Pubertal Timingmentioning
confidence: 99%
“…On the other hand, late maturation increased fracture risk (Zhu and Chan 2017) and psychopathology in boys in terms of higher rates of depressive symptoms and disruptive behaviours (Graber 2013;Zhu and Chan 2017). Aside from its health impact, recent evidence suggests that pubertal timing has cognitive effects which may be reflected in academic performance (Cavanagh et al 2007;Martin and Steinbeck 2017) and educational outcomes (Koivusilta and Rimpel€ a 2004;Koerselman and Pekkarinen 2017), influencing socioeconomic conditions in adulthood (Johnson et al 2011;Koerselman and Pekkarinen 2017).…”
Section: Introductionmentioning
confidence: 99%